Inhibitory Effect of Andrographis paniculata Lactone on Staphylococcus aureus α-Hemolysin - Wang, Xin; Ma, Qiang; Niu, Xiaohao; Liu, Zhu; Kang, Xinyun; Mao, Yanni; Li, Na; Wang, Guiqin (Frontiers in Pharmacology, 2022)
We investigated the effect of andrographolide (AP) on the hemolytic capacity of Staphylococcus aureus (S. aureus) isolated from our region. AP is a labdane diterpenoid isolated from the stem and leaves of Andrographis paniculata. The hla gene from 234 S. aureus strains and the quality control standard strain ATCC29213 in dairy cows in some areas of Ningxia was analyzed. Evolutionary analysis, homology modeling, and functional enrichment annotation of α-hemolysin Hla detected from our region were performed through bioinformatics. The hemolytic ability of S. aureus isolates from the region was examined using the hemolysis test, and the effect of AP on S. aureus was quantified. Moreover, the effect of AP on the transcript levels of hla and genes highly related to hla (i.e., clfA and fnbA) was examined through fluorescence quantitative PCR. The mode of action of AP on the detected Hla was analyzed through molecular docking and kinetic simulation. The results showed that S. aureus in our region has a high rate of hla carriage. The hemolytic activity of strains NM98 and XF10 was significant, and ATCC29213 also exhibited some hemolytic activity. AP could inhibit Hla expression by downregulating hla, clfA, and fnbA transcript levels, which in turn attenuated the S. aureus hemolytic activity. Meanwhile, the AP molecule can form three hydrogen bonds with amino acid residues ASN105, SER106, and THR155 of Hla protein; bind with PRO103 through alkyl intermolecular forces; and form π-bonds with LYS154, reflecting that the AP molecule has a comparatively ideal theoretical binding activity with Hla protein. Among them, PRO103 and LYS154 are highly conserved in Hla protein molecules and play pivotal roles in the biological functions of Hla, and their binding may affect these functions. Their binding may also prevent the conformational transition of Hla from a monomer to an oligomer, thus inhibiting Hla hemolytic activity. This study offers a molecular basis for use of AP as an antivirulence drug and new ideas for developing novel drugs against S. aureus infection.